ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦2014å±Šå¦ç”Ÿå¯¹æ±‰å—ç¬”ç”»å’Œç»“æž„æŽŒæ¡æƒ…å†µåˆ†æž - Fedora, Pristia Ardra; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractIn Mandarin learning, there are 4 skills which are listening, speaking, reading and writing. Based on the author’s experienced, the most difficult one to learn is writing. The Mandarin script has 3 features, there are shape, pronunciation, meaning, which is clearly different from the Indonesian letters. The author perform a research of analysis on mastering the stroke writing order and the structure of Mandarin characters on students of Tanjungpura University class of 2014 by analyzing the reasons and any difficulties students find in learning Mandarin. Based on the results of the research, the authors conclude the difficulties that often found by students of Tanjungpura University class 2014 on learning to write Mandarin characters was because according to students the Mandarin script was very difficult both to recognized and memorized. Based on the results of the research, students of Tanjungpura University class 2014 did not really mastered the writing of strokes and the structure of Mandarin characters, but the students really mastered the Chinese script structure. The reason of the difficulty in learning mandarin script was because the lack of students in mastering the structure detailed stroke and the order of writing mandarin script. Based on these results, the authors provide some suggestions on learning to write mandarin.Keywords : The stroke order, Chinese script structure, Analysis mastery of writing